Musculoskeletal desmoid tumours: Diagnostic imaging appearances. Issue 4 (13th May 2015) - Liu, Daniel; Perera, Warren; Schlicht, Stephen; Choong, Peter; Slavin, John; Pianta, Marcus
Summary This study aimed to discuss the role medical imaging has on diagnosis of musculoskeletal desmoid tumours and to describe their radiological appearances on various imaging modalities. Imaging of histologically proven cases of desmoid tumours at St. Vincent's Hospital Melbourne were obtained via picture archiving communication system (PACS) and then assessed by two musculoskeletal radiologists. Suitable imagings were obtained from PACS. All imaging chosen was de‐identified. Desmoid tumours can occur in many areas of the body. Imaging plays an important role in the diagnosis of these tumours and magnetic resonance imaging has been the gold standard for imaging and is the most accurate in terms of assessing tumour margins and involvement of surrounding structures.